BEGONIA MAGUNIANA (BEGONIACEAE, BEGONIA SECT. OLIGANDRAE), A NEW SPECIES FROM NEW GUINEA - Wilson, H. P.; Paul, O.; Hughes, M. (Edinburgh Journal of Botany, 2019)
The new species Begonia maguniana H.P.Wilson from New Guinea is described. It is endemic to the Central Range of New Guinea at altitudes of c.1700–2300 m and belongs to the IUCN category Least Concern.
Keywords: Begonia; biodiversity; New Guinea; new species; taxonomy